Teacher Agency in Multilingual Education Policy in an Islamic Boarding School in Indonesia - Muhammad Abdurrizal; Sumardi Sumardi; Kristian Adi Putra (AL-ISHLAH: Jurnal Pendidikan, 2022)
The issue of the role of teacher agency in teacher professional development and school reform has increased significantly over the last decade. This article explores teacher agency in multilingual education policy in an Islamic Boarding School context and how they translated multilingual language policy into their class. Research on teacher agency within multilingual language policies has been widely conducted in public schools in many countries, but in Indonesia, the topic is relatively under-researched. Indonesia has an educational model born from local wisdom and applies multilingualism for student competence, namely Islamic boarding schools. This case exploratory study takes data from 3 teachers from various subjects such as (English, Religion, and Biology) at an Islamic boarding school at the same level as senior high school. Thematic analysis is applied to analyze the phenomenon regarding the multilingual education policy. This study reveals that teachers as agents in multilingual education policies run classes based on beliefs and abilities. Data was collected by interviewing teachers as agents in implementing multilingual education policies. The implication of this research is to provide a reference for education practitioners in adjusting to the implementation of multilingual education.